Crash performance evaluation of a new movable median guardrail on highways. (1st March 2019) - Yang, Jian; Xu, Guoji; Cai, C.S.; Kareem, A.
Highlights: A new movable median guardrail with two optimized major parameters is proposed. It offers a higher level of crash performance than conventional concrete and W-beam guardrails. It exhibits better post collision stability and higher energy absorbing capacity. Abstract: In this study, a new movable median guardrail is proposed to overcome the structural defects of and to improve the low anti-collision performance of two conventional central/ median guardrails comprising of the concrete and W-beam. The design parameters of this movable median guardrail are optimized based on the uniform design method and a linear weighted combination method in accordance with the requirements given in the National Cooperative Highway Research Program (NCHRP) Report 350. This proposed guardrail is systematically evaluated in terms of its energy absorbing capacity, vehicular acceleration, post-impact trajectory of the impacting vehicle, and behavior of the guardrail upon impact through a three dimensional computer simulation using LS-DYNA code. In the evaluation process, performance comparisons of the moveable median guardrail are made with the concrete and W-beam guardrails. The results shows that the performance of the proposed movable median guardrail is superior as compared to the conventional concrete and W-beam guardrails as it offers: a higher level of crash performance is exhibited, the occupants of the impacting vehicle is better protected, and the impacting vehicle exhibits better post collision stability.